1986
DOI: 10.1128/mcb.6.11.4130
|View full text |Cite
|
Sign up to set email alerts
|

In vivo competition of delta-crystallin gene expression by DNA fragments containing a GC box.

Abstract: Expression of the chicken 8-crystallin gene 1 injected into the nuclei of mouse cells is lens specific. Coinjection of GC box-containing DNA fragments from 8-crystallin, simian virus 40 early, and herpes simplex virus type 1 tk promoters effectively suppressed 8-crystallin expression in the lens, but coinjection with DNA fragments not containing the GC box did not. This suppression was likely due to the competition of an Spl-like transcription factor(s) and indicates involvement of the apparently ubiquitous fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0
1

Year Published

1987
1987
1995
1995

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 23 publications
1
6
0
1
Order By: Relevance
“…If B3 or core multimers act as enhancers through interaction with trans-acting nuclear components, there may be competition from cointroduced, excess enhancer segments. We set up conditions for the competition by using microinjection, which allowed us to introduce up to 1,000 copies of an enhancer segment into a nucleus (6). For tkCAT genes without enhancers, injection of 100 cells with an average of 60 gene copies per nucleus resulted in reasonable CAT expression after 24 h (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…If B3 or core multimers act as enhancers through interaction with trans-acting nuclear components, there may be competition from cointroduced, excess enhancer segments. We set up conditions for the competition by using microinjection, which allowed us to introduce up to 1,000 copies of an enhancer segment into a nucleus (6). For tkCAT genes without enhancers, injection of 100 cells with an average of 60 gene copies per nucleus resulted in reasonable CAT expression after 24 h (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These conditions are easily satisfied by microinjection of DNAs into the nucleus. In fact, we were able to demonstrate competition for an Spl-like factor between the GC boxdependent 81-crystallin promoter and a large number of competitor DNA fragments which contained GC boxes which were coinjected (6).…”
mentioning
confidence: 85%
“…2 into the BamHI site (B) to test for an enhancer activity. (B) Promoter and enhancer-promoter complexes to construct the plasmids, p~CAT carries the region -459 bp to + 57 bp of the al-crystallin gene Ohno et al 1985;Hayashi and Kondoh 1986), shown to be sufficient for full promoter activity (Borr~is et al 1985;Hayashi et al 1985;Das and Piatigorsky 1986;Hayashi et al 1985;K. Goto, S. Hayashi, Y. Ueda, and H. Kondoh, in prep.).…”
mentioning
confidence: 99%
“…This observation agrees with the weak involvement of the Spl sites in the ,B1 promoter as observed in the site-specific mutagenesis experiments. Thus, the transcription of the ,B1 gene differs from that of the 81-crystallin gene in a HeLa extract, in which the same competitor essentially eliminated transcription (13), consistent with the involvement of Spl in expression of the 81-crystallin gene (26).…”
Section: Vb1-crystallin Gene Expression 1489mentioning
confidence: 79%